Awareness about Reproductive Health Issues among the Adolescent Girls in a Rural Area of Bangladesh (Bangladesh Journal of Medical Science, 2020)
Background: In Bangladesh there is a scarcity of data on the degree of knowledge amongadolescents about reproductive health.Objective: To assess the awareness about reproductivehealth issues among adolescent girls in a rural area of Bangladesh.Materials and method: Thisdescriptive type of cross sectional study was conducted among 148 adolescent girls who wereselected purposively at PurbaChandara village of Kaliakairthana of Shafipurupazilla of Gazipurdistrict in Bangladesh. A pre-tested semi structured questionnaire was used to collect data byface to face interview.Results: Most of the respondents (76.35%) were within the age group of15-19 years. The average age of their menarche was 14 years. Majority of the respondents 136(91.89%) had history of menstruation and 97 (65.54%) mentioned the duration of menstrualcycle > 7 days. Regarding the hygienic practice during menstruation, majority of them (68.24%)were unhygienic. About knowledge on age at marriage, 131 (88.51%) reportedly mentionedcorrect answer that marriage age is 18 years or more for girls. Regarding the knowledge onfamily planning and family planning methods, most of them (41.89%) had no knowledge.About the infection of reproductive tract, 87 (58.78%) had no knowledge and about half of therespondents (92; 56.79%) had no knowledge about symptoms of STDs.Conclusion: it is ourresponsibility to improve the condition of adolescent girls by giving clear and correct knowledgeon reproductive health which will help them to maintain a good and sound reproductive healthin future.Bangladesh Journal of Medical Science Vol.19(3) 2020 p.567-574